2022
DOI: 10.3390/microorganisms10020261
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Consortia Are Needed to Degrade Soil Pollutants

Abstract: Soil pollution is one of the most serious environmental problems globally due to the weak self-purification ability, long degradation time, and high cost of cleaning soil pollution. The pollutants in the soil can be transported into the human body through water or dust, causing adverse effects on human health. The latest research has shown that the clean-up of soil pollutants through microbial consortium is a very promising method. This review provides an in-depth discussion on the efficient removal, bio-adsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(20 citation statements)
references
References 117 publications
0
20
0
Order By: Relevance
“…Human beings have realized that environmental investments are needed to maintain better world conditions for future generations [ 30 ]. Soil pollution is one of the most serious environmental problems globally due to the weak self-purification ability, long degradation time, and high cost of cleaning soil pollution [ 31 ]. PAHs are widespread in the environment and pose a serious threat to the soil ecosystem [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Human beings have realized that environmental investments are needed to maintain better world conditions for future generations [ 30 ]. Soil pollution is one of the most serious environmental problems globally due to the weak self-purification ability, long degradation time, and high cost of cleaning soil pollution [ 31 ]. PAHs are widespread in the environment and pose a serious threat to the soil ecosystem [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…studies suggested that biodegradation has become a priority for scientific research as it aims to safely and quickly remove for these contaminants from soils [6] and confirmed that the final success of biodegradation depends on the nature of microorganisms which are in direct contact with the biodegradable substance, and that the bio-treatment of soils contaminated with hydrocarbons from crude oil linked to the ability of organisms to consume hydrocarbons [7].…”
Section: Numerousmentioning
confidence: 96%
“…Similarly, conventional technologies for decontaminating the pesticide-polluted sites, such as landfilling, chemical alteration, incineration, composting, etc., are being employed [18]. Due to the various limitations of these methods, such as secondary pollution induction, low-density sludge generation, restricted activity in acidic environments, etc., researchers have focused their attention on using bioremediation technologies that are environmentally friendly, low cost and highly efficient in degrading pollutants [1] The use of various microbial agents, such as bacteria, fungi, yeasts and algae, has received tremendous attention globally to remediate different matrixes contaminated with heavy metals and persistent organic pollutants [19]. Microbial remediation represents the most suitable and preferential technique in the current times of both environmental and economic crises, chiefly in developing countries.…”
Section: Introductionmentioning
confidence: 99%